2015
DOI: 10.4161/21624011.2014.965570
|View full text |Cite
|
Sign up to set email alerts
|

Distinct patterns of intratumoral immune cell infiltrates in patients with HPV-associated compared to non-virally induced head and neck squamous cell carcinoma

Abstract: Human papillomavirus (HPV) infection is one of the most important etiologic causes of oropharyngeal head and neck squamous cell carcinoma (HNSCC). Patients with HPV-positive HNSCC were reported to have a better clinical outcome than patients with HPV-negative cancers. However, little is known about the possible causes of different clinical outcomes. In this study, we analyzed a detailed immune profile of tumor samples from HNSCC patients with respect to their HPV status. We analyzed the characteristics of immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
206
1
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(242 citation statements)
references
References 54 publications
14
206
1
11
Order By: Relevance
“…Expression of β 2 -microglobulin, MHC class I heavy chain, and large multifunctional peptidase 10 was quantified, and all data were correlated with patient outcome. We found that, consistent with previous reports, high numbers of CD8 + T cells at the invasive margin correlated significantly with prolonged overall survival (OS), while the number of increased T and B cell infiltrates, higher levels of IFN-γ secretion, and increased numbers of FoxP3 + T cells, all features of antiviral responses that may translate into enhanced antitumor immune responses (22)(23)(24)(25)(26), distinguishing HPV + and HPV -tumors is essential (17,27). Immune surveillance is mediated by the composition of the tumor microenvironment (TME); it is affected by a multitude of strategies tumors use to escape immune recognition.…”
Section: Introductionsupporting
confidence: 78%
“…Expression of β 2 -microglobulin, MHC class I heavy chain, and large multifunctional peptidase 10 was quantified, and all data were correlated with patient outcome. We found that, consistent with previous reports, high numbers of CD8 + T cells at the invasive margin correlated significantly with prolonged overall survival (OS), while the number of increased T and B cell infiltrates, higher levels of IFN-γ secretion, and increased numbers of FoxP3 + T cells, all features of antiviral responses that may translate into enhanced antitumor immune responses (22)(23)(24)(25)(26), distinguishing HPV + and HPV -tumors is essential (17,27). Immune surveillance is mediated by the composition of the tumor microenvironment (TME); it is affected by a multitude of strategies tumors use to escape immune recognition.…”
Section: Introductionsupporting
confidence: 78%
“…Some reports have shown a decrease of tumor-infiltrating lymphocytes (TIL) in HNSCC, 9 but the clinical outcome seems to depend more on the type of TIL rather than on their total number. For instance, cytotoxic CD8 C T cells are significantly decreased in HNSCC patients if compared with healthy controls, [9][10][11][12][13][14][15] probably due to an increase apoptotic rate among this cell population in HNSCC. 13 On the top of that T cells isolated from HNSCC patients are significantly less responsive to in vitro stimulation than those isolated from healthy controls.…”
Section: Hnscc and Immune Escapementioning
confidence: 99%
“…28 A recent study indicated that different patterns of intratumor immune cell infiltrates in HPVC HNSCC compared with HPV¡ HNSCC. 29 Interestingly, we found that CD8 C / CTLA4 remained correlated with the immunosuppressive cell population in HPV¡ HNSCC.…”
Section: Discussionmentioning
confidence: 64%